PEMBERDAYAAN ANAK DAN REMAJA PEREMPUAN MELALUI PEMBELAJARAN BAHASA INGGRIS DI DESA GOLONG, KEC. NARMADA MENGGUNAKAN PENDEKATAN COLLABORATIVE LEARNING - Puspita Dewi; Nurul Hidayah; Isra Dewi Kuntary Ibrahim; Baiq Fitria Rahmiati; Sirojul Hadi (LPPM Universitas Flores, 2021)
Various issues in villages become one of the obligations of academicians or lecturers to solve the problems faced by society. Golong is a village that has the uniqueness and opportunity to be a developed village both for natural resources and human resources. Even though the society has low income but the spirit of the society is high. Therefore, community service team initiates to guide in learning English for children and women teenagers in Golong, Narmada, and West Lombok. Collaborative learning is one of the methods used in this community service activity because it involves and provides plenty opportunity to the learners for sharing and discussing of the materials and to solve the matters. Consequently, by applying the collaborative learning approach, the learners are expected to be more active in learning and cooperating so that their habits of learning and collaboration to be implemented by the learners in workplaces. The community service results show that guidance and empowerment in learning English have a positive impact and have a good response from the learners and community. The empowerment has a pivotal role in encouraging the learners’ motivation and improves the learners’ achievements. The community service activity is expected to be able to be sustainable and become one of cooperation between institutions and villages so that the institution contributes to shape the society to be smart, wise, and prosperous.